MOTIVASI PEMBELAJARAN PADA SURAT AL-KAUTSAR (STUDI ANALISIS MAKNA DALAM PERSPEKTIF PEMIKIRAN DR. KH. ABDUL SYAKUR YASIN) - Sumarta, Sumarta (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2023)
In the Al-Quran there are not only legal verses (kauniyah) but in the Al-Quran there are very many pearls of wisdom that can be used as motivation in this life. Many well-known motivators in the world steal and quoting from the Al-Quran. Meanwhile, Muslims make the Al-Quran as a decoration and a complement. One of the many pearls of the Al-Quran is Surah Al Kautsar, in addition to its short verses it is also easy to memorize and remember. This paper discusses the interpretation of the verses in Surat Al Kautsar according to the perspective of thought and interpretation of Dr. KH Abdul Syakur Yasin, MA. With the approach of analyzing the meaning of language (linguistics) in the context of contemporary social conditions.